Identifikasi Hambatan Belajar Siswa pada Topik Pergeseran Kesetimbangan Kimia di Madrasah Aliyah Negeri 3 Pekanbaru - Sukeimi Sukeimi (Anotero Lembaga Scientific Pekanbaru, 2022)
This study aims to identify student learning barriers on the topic of Chemical Equilibrium Shifts. This research is a descriptive analysis research. This research was conducted in class XI MAN 3 Pekanbaru with a total of 30 students. Data collection in the study was carried out using document studies, observation, and interviews. The data obtained were then analyzed using a descriptive interpretive method. Based on data analysis, it can be seen that learning barriers are caused by previous learning experiences that familiarize students with memorizing concepts so that they are not familiar with problems that require higher analytical thinking skills. And due to the limitations of students' understanding of contextual applications and concepts. Based on the analysis of the findings and discussion, the conclusions that can be obtained are that the learning barriers identified on the topic of chemical equilibrium shifts in this study are didactic and epistemological.